Role of alpha-ketoglutarate and (pro)renin receptor in intra-renal angiotensin II formation, Na+ reabsorption and blood pressure in diabetic disease. - Gonzalez - Parra; Alexis (2023)
PROJECT RESULTS: In the original proposal we planned to answer the following questions: • Does streptozotocin (STZ)-induced type I diabetic mice having high plasma and urinary glucose have increased PRR expression via aKG-activation of OXGR1? Does OXGR1 antagonism prevent tubular Ang II formation, Na+ reabsorption and high blood pressure (BP)? • Does HG increase aKG release in vitro via GLUT1? Does aKG increases PRR expression via OXGR1 and activation of PKC and Ca2+ in vitro? • Does CD PRR contribute to tubular Ang II formation, Na+ reabsorption and elevations in BP in STZ diabetic mice? We will answer this by using wild type mice and CD-PRR knockout mice (CDPRR-KO) subjected or not to STZ-induced type I diabetes. In the following pages we summarize the main results: 1. STZ-induced hyperglycemia was associated with increased urinary a-ketoglutarate. As shown in Figure 1A STZ mice have reduced body weight at day 6. Mice treated with the OXGR1 antagonist ML also showed a significant reduction in body weight. Reduction in body weight was also confirmed and standardized by measuring body weight versus tibia-length ratio. Mice treated only with ML did not show changes in body weight. Fasting blood glucose levels were significantly higher on day 6 in STZ-induced hyperglycemic mice compared to controls. Fasting blood glucose was not altered in mice treated with ML when compared to normoglycemic control mice (Figure 1B). Urinary levels of aKG assessed by aKG/creatinine ratio were significantly augmented in STZ and STZ+ML groups on day 6 as compared to controls (Figure 1C). Since STZ animals had reduced body weight, we evaluated food intake in 24h metabolic cages measurements. No differences were found in food intake on days 1, 3 and 6 between controls, STZ and STZ plus ML (Figure 1D). As shown in Figure 1E, water intake was significantly greater in diabetic mice (STZ alone and STZ+ML treatment) compared to control mice on day 6. No effect was observed in ML group. Of note, diuresis was significantly higher in STZ mice ...